Effect of acupuncture on primary hypothyroidism and irregular menstruation in infertile women: a randomised controlled study - Eman Sedky Abdullah; Abeer Mohamed ElDeeb; Eman Ahmed Sultan; Hassan Omar Ghareib; Salwa Mostafa EL-Badry (Physiotherapy Quarterly)
Introduction This study aimed to examine the impact of acupuncture and a low-caloric diet on primary hypothyroidism and irregular menstruation in infertile women.